فكر الشيخ الأكبر محي الدين بن عربي وأثره عند العرب والغرب المستشرقين - حكيمة, بوشلالق (جامعة الوادي - University of Eloued, 2021)
لقد حظي التصوف باهتمام كبير وجاد من قبل الباحثين والدارسين للتراث العربي الإسلامـي عامـة ولشعـر التصوف خاصـة، وكـان الاهتمام البالـغ للشعـراء المتصوفـة، والتركيز الكبير عليهم في محاولــة فهم لغتهم الشعريـة، وخاصـة شعر الشاعـر والمؤلف الصوفي المتفلسف الكبير الشيخ مُحي الدين بن عربي وفكره الذي كان له بالغ الأثر على النقـاد العرب والغرب ، وخاصـة المستشرقين قديما وحديث، وألَّفـوا حولـه الآلاف مــن التأليف والشروحات على كتبه التي بثَّ فيها الكثير من القضايـا الفلسفيـة والصوفيـة التي يصعب حصرها وضبط إيقاعها، مما يجعل الوقوف عليها في غاية الصعوبة Mysticism has got a great and serious interest by researchers and scholars of the Arab Islamic patrimony in general and the mystical poetry in particular. The great interest in mystical poets and the great focus on them was an attempt to understand their poetic language, especially the poem of the great mystical philosopher, author, and poet the Shaikh Mehei Eddin Ben Arabi and his thought’s great impact on the Arab and Western critics, particularly the orientalists, of ancient and present time, whose works are considered as an explanation for his books containing many philosophical and mystical matters, which are difficult to be limited and their rhythm is difficult to be adjusted, therefore they’re so hard to be understood.
مقال
Keywords: حي الدين بن عربي ؛التصوف؛ الفكر؛ الاستشراق؛ الفلسفة الإسلاميةy; . Mehie Eddin Ben Arabi.mysticism.intellectuality.Orientalisme.the Islamic philosoph